Before I go to sleep [videorecording (DVD)] - Joffe, Rowan; Kidman, Nicole, 1967-; Firth, Colin, 1960-; Strong, Mark, 1963- (20th Century Fox Home Entertainment, 2014)
After an accident leaves her with a serious head injury, a woman wakes up remembering nothing of her past. As secrets are revealed she starts to question the people closest to her.